(3HMhK GdJShjb (B:s (3CSGS GdeQGMd hGdJWHjbGJ (B/s - (3YHjOGJ, eMeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2000)
(3ebOeI aj HMhK GdJShjb(B-(3CSGSjGJ hCfhGY hNUGFU hefGgL GdHMK GdYdej(B-(3CfhGY heUGOQ GdMUhd Ydi GdHjGfGJ(B-(3CSGdjH LeY GdHjGfGJ(B-(3GdYjfGJ hWQb GNJjGQgG(B-(3JUeje GSJeGQI GdESJbUGA(B-(3GdHMhK GdfhYjI(B-(3eSJhjGJ hCfhGY GdbjGS hGdeYGjjQ GdaYGdI(B-(3LeY GdHjGfGJ(B-(3JMdjd GdHjGfGJ GMUGFjG(B-(3GYOGO GdJbQjQ GdfgGFj(B-(3JWHjbGJ YedjI aj GdJShjb hSdhc GdeSJgdcs
Keywords: (3GdJShjbs; (3GdJShjb(B- (3HMhKs; (3GdWQb GdEMUGFjIs